Pengetahuan dan Sikap Mahasiswa Berorganisasi terhadap Kesehatan Mental di Fakultas Pertanian Universitas Siliwangi - Aisyah Salsabila Binawan; Ega Oktaviona Putri; Ilma Amaliyyah Rahmat; Kaila Nisrina Wahyu Darodjat; Nira Qurrotul Aini; Raisa Azkia Utami; Sausan Karimah; Syifa Rahmawati; Kharisma Nurul Fazrianti Rusman (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
This study aimed to analyze the influence of a mental health education intervention on the knowledge and attitudes of student organization members at the Faculty of Agriculture, Universitas Siliwangi. The intervention, which included educational sessions and group discussions, was conducted on 22 April 2025 and involved 15 student participants from two student organizations. A pre-test and post-test were administered to measure changes in knowledge and attitudes. The Wilcoxon test showed a significant improvement (p = 0.022) in knowledge scores after the intervention. Attitudes also shifted positively, particularly in aspects of peer support, stress awareness, and healthy lifestyles. The findings indicate that community-based interventions in student organizations can effectively promote mental health literacy and supportive behaviors. The program is recommended for continuation and expansion to sustain its benefit